Adapting Wine Grape Ripening to Global Change Requires a Multi-Trait Approach - Suter, Bruno; Destrac Irvine, Agnes; Gowdy, Mark; Dai, Zhanwu; van Leeuwen, Cornelis (Frontiers in Plant Science, 2021)
In winegrowing regions around the world increasing temperature associated with climate change is responsible for earlier harvests and is implicated in undesirably high sugar concentrations at harvest. Determining the suitability of grapevine varieties in existing or new winegrowing areas has often been based on temperature, without considering other factors. The purpose of this study was to quantify key berry sugar accumulation traits and characterize their plasticity in response to several climate variables. Data was collected from 36 different cultivars over years (2012-2018) from an experimental vineyard in Bordeaux, France. Sugar amounts were obtained through weekly berry sampling from mid-véraison on and continued until after technological maturity. The variation in sugar accumulation traits for all cultivars, when considered together, were well explained by cultivar, year, and their interaction, highlighting the relative roles of genetic variation and phenotypic plasticity. Sugar accumulation traits were affected by antecedent and concurrent climate factors such as photosynthetically active radiation, temperature, and vine water status, whether before, or after mid-véraison. In addition, other traits such as berry weight at mid-véraison and date of mid-véraison had an important influence on sugar accumulation traits. More notably, the relative importance of these factors varied significantly by cultivar. The specific physiological mechanisms driving the plasticity of these traits remain to be identified. Adaptation to climate change cannot be based on temperature alone and crop responses cannot be generalized across genotypes, even within species.